PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SUNSCREEN AZARINE MELALUI CELEBRITY ENDORSMENT SEBAGAI VARIABEL INTERVENING - Annisa Aulia Putri; Alida Palilati; Sinarwaty; Yusuf; Sabri; La Harjoprawiro (Jurnal Manajemen dan Kewirausahaan, 2024)
This research aims to determine the simultaneous and partial influence of Product Quality variables on the decision to purchase Azarine sunscreen through Celebrity Endorsement as an Intervening variable on the social media of the people of Kendari City. The population in this study was all Kendari City residents who had purchased Azarine sunscreen products. The sample in this study was 65 respondents. The sampling technique in this research used accidental sampling. The data collection method in this research is by questionnaire. The instrument tests used are validity and reliability tests. The analysis technique used is Structural Equation Modeling (SEM)-PLS analysis.The research results show that: (1). Product quality has a positive and significant effect on purchasing decisions . (2). Product quality has a positive and significant effect on Celebrity Endorsement. (3). Celebrity Endorsements have a positive and significant effect on purchasing decisions.(4) Product quality has a positive and significant effect on purchasing decisions through celebrity endorsements as an intervening variable